Математическое моделирование электромагнитных характеристик электротехнических сталей - Пуйло, Г.В.; Насыпанная, Е.П.; Левин, Д.М. (Електротехніка і електромеханіка, 2011)
The necessity of mathematical simulation and computer-assisted forming of analytical models for electric steels electromagnetic characteristics with the purpose of research designing, synthesis, analysis and optimization of electrical devices is grounded. Requirements for these mathematical models are formulated, an algorithm of their computer-assisted forming on the basis of flat approximating functions with an exponential kernel developed, which allows obtaining mathematical models in the form of repeatedly differentiable functions that satisfy specified requirements for the approximation accuracy.